Galactose as inducer of the production of extracellular polymeric substances by Acidithiobacillus ferrooxidans - Saavedra Olaya, Albert Ulises (2013)
The presence of extracellular polymeric substances (EPS) is important in the building of biofilms on mineral surfaces, increasing the bioleaching activity, as well as protecting the cells from adverse environmental conditions. The objective of this work was to study the effect of galactose in EPS production by Acidithiobacillus ferrooxidans. The experiences were performed in shake flask of 250 mL at 30 °C, 200 rpm and at an initial pH of 1.8. In order to establish the natural tolerance of the strain, its growth behaviour was evaluated at high ferric iron concentrations by adding consecutively the equivalent of 9 g/L of ferrous iron each time it was depleted in the broth. Cell growth stopped once ferric iron concentration increased up to 38 g/L. In order to determine the optimal conditions for EPS production, experiments were run in a chemostat of 0.5 L, operated at a constant dilution rate of 0.03 h-1. Different steady states were obtained varying feeding concentrations of galactose (0.15%; 0.25% and 0.35%) and carbon dioxide (180 ppm and 360 ppm). , Cells grown in the chemostat at optimum operation conditions were used as inoculum to determine oxidative capacity of the microorganisms overproducing EPS. The EPS was quantified using confocal laser scanning microscopy (CLSM), labelling the cells with propidium iodide and EPS carbohydrates with wheat germ agglutinin (WGA). The higher volume production of EPS was observed in cells grown using 360 ppm of CO2 and 0.35% of galactose. Also it was observed a size increment of cells, compared to cells grown in culture medium having 9 g/L of ferrous iron where presence of EPS was no detected. The results revealed that EPS overproducing A. ferrooxidans showed a tolerance to ferric iron concentration almost 9.5 g/L higher than the natural tolerance of cells grown in absence of galactose. Presence of galactose in culture medium stimulated the EPS production.